Eksistensi Pabbagang Ponrang Kabupaten Luwu 1970-2016 - Tantri Wulandari; Muh. Rasyid Ridha; Najamuddin Najamuddin (PATTINGALLOANG, 2017)
This paper examines the existence Pabbagang In the village of the District Ponrang Ponrang Luwu Regency (1970-2016). The results of this study on Ponrang Pabbagang in the village at the time and the traditional era, the modern age and socio-economic life and system for the results. This research shows the beginning where pabbagang Village Ponrang, the origin of the naming Pabbagang and discuss the performance of pabbagang traditional performance pabbagang modern as well as how the system of revenue sharing between the owners of capital or owner bagang in every era with pabbagang itself where the system for the results in applied is tesan system, and how the competition between traditional pabbagang with modern pabbagang, and work system in laukan by pabbagang when in the butterflyfish (marine). The main fishing gear being the principal fishing gear used by the fishing village of Ponrang namely Bagang, where in the era of traditional fishermen using bagang step while in the modern era using motion bagang Ponrang village in which the people call Bagang Rambo. and the village social system Pabbagang Ponrang influenced by everyday life of fishermen at the time of the search process fish, In the 1980s Ponrang Pabbagang society has entered the modern era where fishermen are already using modern fishing gear as well. since the social and economic life has improved, and the result of it is also the case that fundamental changes in lifestyle Ponrang village society especially those who cultivate the profession as a fisherman pabbagang or in terms of economic level of society. and the village social system Pabbagang Ponrang influenced by everyday life of fishermen at the time of the search process fish, In the 1980s Ponrang Pabbagang society has entered the modern era where fishermen are already using modern fishing gear as well. since the social and economic life has improved, and the result of it is also the case that fundamental changes in lifestyle Ponrang village society especially those who cultivate the profession as a fisherman pabbagang or in terms of economic level of society. and the village social system Pabbagang Ponrang influenced by everyday life of fishermen at the time of the search process fish, In the 1980s Ponrang Pabbagang society has entered the modern era where fishermen are already using modern fishing gear as well. since the social and economic life has improved, and the result of it is also the case that fundamental changes in lifestyle Ponrang village society especially those who cultivate the profession as a fisherman pabbagang or in terms of economic level of society.  This research is descriptive analysis using historical methods, through the stages of the stages of work which includes; Heusristik, interpretation and Histriografi criticism. As the concept of Social Sciences sociology used to analyze the relevant issues, particularly in assessing the socio-economic life associated with changes in social life in fishing communities